Las organizaciones de Economía Popular y Solidaria y el Estado: una relación que asegura la sostenibilidad: estudio del Centro Comunitario Floreana Provincia de Galápagos - Bravo Segovia, Rosa Elvira (2018)
The main interest of this investigation is to analyze the relationship between the popular and solidarity economy organizations and the State, with the aim to set up the factors that interfere in the daily actions and determine its sustainability. The central theme turns around the organizations of the real sector, the state intervention in their actions and the caused effects, emphasizing the strategies developed by them to look forward in defense of their membership. Semi-structured interviews, focus groups, and participant observation were applied to the members of the organization; In addition, a through bibliographic review was taken. As a result, it was established that the organization opted for organizational strategies in order to rise its objectives. This investigation is shown as an input for the deployment of public policies, since the decision makers have as their mission to ensure the sustainability of the popular and solidarity economy organizations.